Legal Analysis of Smart Contracts as Electronic Agreements under Civil and Electronic Transactions Law - Adilla Meytiara I.; Kurdi; Teuku Ahmad Dadek (Jurnal Hukum Magnum Opus, 2026)
The development of Distributed Ledger Technology (DLT) and blockchain has given rise to disruptive innovations in the form of smart contracts. On the one hand, this technology offers superior efficiency, autonomy, transparency, and security compared to conventional contracts. On the other hand, the deterministic, automatic, and rigid nature of the code poses fundamental challenges to the Indonesian civil law framework, particularly the Civil Code (KUHPerdata), which is flexible and prioritizes principles such as good faith and protection against defects of consent (wilsgebreken). This study aims to analyze the position of smart contracts as valid agreements according to the requirements in Article 1320 of the Civil Code, as well as to examine how the Electronic Information and Transaction Law (EIT Law) and its implementing regulations, including the latest recognition in the Financial Sector Development and Strengthening Law (P2SK Law), provide legitimacy and legal certainty. This study uses a normative legal research method with a statute approach and a conceptual approach. The results of the study show that smart contracts can fulfill the requirements for a valid agreement (Article 1320 of the Civil Code) with the following caveats: the main challenge lies in fulfilling the subjective requirements (competence and agreement), which require an off-chain identity verification mechanism and separation between the agreement (natural language) and the code (execution tool).